2011
DOI: 10.1038/ajh.2010.239
|View full text |Cite
|
Sign up to set email alerts
|

Globular and Full-Length Adiponectin Induce NO-Dependent Vasodilation in Resistance Arteries of Zucker Lean but Not Zucker Diabetic Fatty Rats

Abstract: Adiponectin exerts a NO-dependent vasodilation in resistance arteries of normoglycemic ZL rats, but not diabetic ZDF rats. This may contribute to endothelial dysfunction in ZDF rats. Alterations in the expression of APPL1 may be involved in the observed insensitivity to adiponectin in ZDF rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 40 publications
1
39
1
3
Order By: Relevance
“…Globular adiponectin likewise was shown to increase eNOS activity and additionally stimulate eNOS expression (Hattori et al 2003). Both forms of adiponectin can thus influence vasodilation (Schmid et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Globular adiponectin likewise was shown to increase eNOS activity and additionally stimulate eNOS expression (Hattori et al 2003). Both forms of adiponectin can thus influence vasodilation (Schmid et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This observation could be expected based on related literature (8,12,36,42) demonstrating insulin sensitizing actions of APPL1 in liver and skeletal muscle. Indeed, APPL1 levels were significantly decreased in endothelium of Zucker diabetic fatty rats (38), and a recent study suggested that chronic exercise in mice increased hepatic APPL1 expression, which, at least in part, accounted for improved insulin sensitivity (28). However, in a human study, there was higher APPL1 expression in type 2 diabetic muscle, and weight loss in these individuals was associated with reduced skeletal muscle APPL1 level (22).…”
Section: E801mentioning
confidence: 89%
“…Adiponectin is a potent vasodilator and, similar to insulin, its vasodilatory effect is mediated via a NO-dependent mechanism (Cheng et al, 2007; Schmid et al, 2011; Xi et al, 2005). Inasmuch as adiponetin’s vasodilatory actions have been repeatedly demonstrated in conduit arteries and resistance arterioles (Cheng et al, 2007; Schmid et al, 2011; Xi et al, 2005), its effect on the microvasculature was unknown prior to our recent study published in Circulation Research(Zhao et al, 2013).…”
Section: Crosstalk Between Adiponectin and Insulin: The Microvascularmentioning
confidence: 99%
“…Unlike other adipokines, ample evidence from both laboratory animal and human studies has confirmed that adiponectin has an insulin-sensitizing action and its levels are decreased in animals or humans with obesity and insulin resistance (Arita et al, 1999; Berg et al, 2001; Combs et al, 2001; Fruebis et al, 2001; Hotta et al, 2000; Kadowaki et al, 2006; Weyer et al, 2001; Yamauchi et al, 2001). Furthermore, adiponectin exerts a beneficial effect on the cardiovascular system (Fesus et al, 2007) and hypoadiponectinemia is independently associated with endothelial dysfunction in both humans and animals (Cao et al, 2009; Iwashima et al, 2004; Kumada et al, 2003; Ouchi et al, 2003; Schmid et al, 2011; Tan et al, 2004; Torigoe et al, 2007). …”
Section: Introductionmentioning
confidence: 99%